1955
DOI: 10.1021/j150534a009
|View full text |Cite
|
Sign up to set email alerts
|

Pressure–Temperature–Composition of Rare Earth–Hydrogen,Systems

Abstract: Pressure-temperature-composition data are presented for the lanthanum-, cerium-, praseodymium-and neodymiumhydrogen systems in the ranges T = 150 to 800°, p = 0.01 to 400 mm. It is concluded that La, Ce, Pr and Nd all behave similarly with hydrogen, exhibiting two solid phases, metal and a hydride phase, for compositions between M and MIL, and a single solid hydride phase for compositions between MIL and approximately ». (M = La, Ce, Pr or Nd.) In the latter range, composition is dependent on temperature and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1960
1960
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(22 citation statements)
references
References 1 publication
1
21
0
Order By: Relevance
“…For this purpose a deuterated lanthanum sample was examined by in-situ neutron powder diffraction as a function of deuterium pressure, and ab initio calculations were performed. Phase diagram data [6,7] suggested that temperatures close to 550 K and pressures between ∼ 10 −2 mbar and 10 bar provide a favourable pressure-composition regime for such a study.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose a deuterated lanthanum sample was examined by in-situ neutron powder diffraction as a function of deuterium pressure, and ab initio calculations were performed. Phase diagram data [6,7] suggested that temperatures close to 550 K and pressures between ∼ 10 −2 mbar and 10 bar provide a favourable pressure-composition regime for such a study.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work investigating hydride formation often used high hydrogen pressures and a variety of temperatures [1,3,11]. Reactions were also left for several days.…”
Section: Discussionmentioning
confidence: 99%
“…The level of hydriding that occurs is strongly dependent upon the pre-treatment temperature and the pressure of hydrogen gas during the reaction [1]. Once prepared, lanthanide hydrides generally have relatively high hydrogen retention as well as high melting points.…”
Section: Introductionmentioning
confidence: 99%
“…and Simon and Lange [42] (l0°to 13°K) . Using the data of Simon [ 41 ] and Simon and Lange [42], Kelley and King [20] calculated SRgg -Sg = 10.35 ±0.10 eu for Si02 glass.…”
Section: !Yomentioning
confidence: 93%
“…Using the data of Simon [ 41 ] and Simon and Lange [42], Kelley and King [20] calculated SRgg -Sg = 10.35 ±0.10 eu for Si02 glass. Westrum [ 5 ] lists as unpuMished measurements on the heat capacity of SIO 2 glass in the range 6°t o 300°K.…”
Section: !Yomentioning
confidence: 99%